Exploring The Potential of Human Papilloma Virus: An Overview - Gopinath Ramalingam; M Arundadhi; R Revathi; Sowndarya Vijay; A Dhanasezhian; G Sucila Thangam (Medsci Publications, 2023)
Human papillomavirus (HPV) infection is the most frequent viral sexually transmitted infection in the world. HPV is currently the most prevalent infection responsible for female cancers, with more than 90% of cervical cancers - the fourth deadliest malignancy in women- having been diagnosed. Additionally, genital and upper aerodigestive tract malignancies, as well as cutaneous and anogenital warts, are also linked to HPV infection. Cervical screening programs that are organized have the potential to be more effective than opportunistic screening programs. Nonetheless, screening programs have consistently been linked to lower cervical cancer incidence and mortality. Over the last 40 years, developed countries have achieved such a reduction in cervical cancer incidence and mortality. This is largely because of organized cytological screening and immunization programs. In women with no indication of previous or current HPV infection, HPV vaccinations are very efficient at preventing infection and illnesses caused by vaccine-specific genotypes. Despite the effective implementation of the HPV vaccination program in many nations around the world, challenges with HPV prevention and treatment of linked diseases will persist in developing and poor countries. This review provides an insight into various aspects of HPV infection.